Comparative characterisation of durian, mango and avocado - Sumitra Poovarodom (2018)
The aim of this investigation was to determine the nutritional and bioactive properties of relatively less investigated exotic fruit durian (Durio zibethinus Murr.) and to compare these indices with widely used mango (Mangifera indica L.) and avocado (Persea americana). For this purpose HPLC, three-dimensional fluorescence (3D-FL), several radical scavenging assays and multivariate factor analysis were used. It was found a similarity in acetone extracts between durian and mango in the contents of polyphenols (1.66 ± 0.08, 1.48 ± 0.05, mg GAE g-1DW, respectively), and in some antioxidant assays such as ABTS (11.98 ± 0.5, 12.24 ± 0.5, lm TE g-1DW, respectively) and DPPH (5.61 ± 0.3, 5.22 ± 0.2, lm TE g-1DW, respectively). Durian and avocado were similar in the contents of polyphenols, and ABTS and DPPH values in water and in methanol extracts, respectively. Based on the obtained results the nutritional and bioactive properties of durian are comparable with those indices in mango and avocado. In conclusion, durian can be recommended as a part of disease prevented diets. © 2010 The Authors. Journal compilation © 2010 Institute of Food Science and Technology.